Methodology for Assessing the Quality of Agribusiness Activity Based on the Environmentally Responsible Approach - Anfinogentova, Anna Antonovna; Dudin, Mikhail Nikolaevich; Lyasnikov, Nikolai Vasilievich; Protsenko, Oleg Dmitrievich (Economy of Regions, 2017)
The article is devoted to the research and development of quality evaluation methods of agro-industrial enterprises activity in the regional economy with the use of the ecological approach. The hypothesis of the study is that the activity of the economic entities (as well as of agribusiness) must be assessed not only in the context of economic efficiency and effectiveness, but also in the context of environmental ethics and environmental aggression. As the initial data, we have used the indicators of economic statistics of Russian agrarian-oriented regions, as well as the data received from management reporting on the sample of enterprises of three regions (the Belgorod and Moscow regions, Krasnodar Territory). The article offers the economic and mathematical approach for measuring the level of the environmental responsibility of agro-industrial enterprises on the basic formula of the Mandelbrot set and statistical indicator of Hurst. Our scientific contribution is the development of a modified methodology for assessing the quality of the activity of agro-industrial enterprises using the parameter characterizing the level of environmental ethics and environmental aggression of these entities. The main result of the study is the approbation of the method, which has shown its practical applicability and relative coherence with certain indicators of regional ecological statistics. The proposed method is characterized by the integration of the different mathematical approaches and as an adaptive assessment tool that can be used to assess the quality of the activity of both agro-industrial enterprises and enterprises of other industries and fields of the economy. In the further works, the authors plan to develop methodological approaches to the assessment of the quality of agro-industrial products. At the same time, the main attention will be paid to the ecological and social component of the quality.